THE GRAM-SCHMIDT PROCESS IN AN INDEFINITE INNER PRODUCT SPACE - HUMAIRA (NIM: 10114069), SITI
One generalization of the inner product is known as the indefinite inner product. The properties of the inner product space, such ortogonality can be brought to the indefinite inner product spaces , including the Gram-Schmidt process. However, not all linearly independent set in the indefinite inner product space can be converted into orthonormal sets. Therefore, in this final project is further discussed the necessary and sufficient conditions in the linear independent set in an indefinite inner product space in order that the set can be converted into an orthonormal se by utilizing the Gram-Schmidt process.